Designing Cyclometalated Ruthenium(II) Complexes for Anodic Electropolymerization. Issue 8 (23rd January 2014) - Friebe, Christian; Schulze, Benjamin; Görls, Helmar; Jäger, Michael; Schubert, Ulrich S.
Abstract The anodic electropolymerization of thiophene‐functionalized cyclometalated ruthenium(II) complexes is shown for the first time. Oxidative decomposition reactions can be overcome by modification of the involved redox potentials through the introduction of electron‐withdrawing substituents, namely nitro groups, at the cyclometalating phenyl ring. The generated functionalized ruthenium(II) complexes allow the electrochemical preparation of thin polymer films, which show a broad UV/Vis absorption as well as reversible redox switchability. The presented complexes are promising candidates for future photovoltaic applications based on photo‐redox‐active films.